Targets and Mechanism Used by Cinnamaldehyde, the Main Active Ingredient in Cinnamon, in the Treatment of Breast Cancer - Liu, Yufei; An, Tian; Wan, Donggui; Yu, Bowen; Fan, Yingyi; Pei, Xiaohua (Frontiers in Pharmacology, 2020)
Background: Breast cancer has become one of the most common malignant tumors in women owing to its increasing incidence each year. Clinical studies have shown that Cinnamomum cassia (L.) J. Presl (cinnamon) has a positive influence on the prevention and treatment of breast cancer. Aim: We aimed to screen the potential targets of cinnamon in the treatment of breast cancer through network pharmacology and explore its potential therapeutic mechanism through cell experiments. Methods: We used the TCMSP, TCM Database @ Taiwan, and TCMID websites and established the active ingredient and target database of cinnamon. Thereafter, we used the GeneCards and OMIM databases to establish a breast cancer-related target database, which matched the cinnamon target database. Based on the matching results, the STRING database was used to analyze the interaction between the targets, and the biological information annotation database was used to analyze the biological process of the target (gene ontology, GO) and the pathway enrichment of Kyoto Encyclopedia of Genes and Genomes (KEGG). After establishing the layout of the analysis, we used Cytoscape 3.6.0 software for network analysis. Finally, the cell experiment was used to verify the anti-breast cancer effect of cinnamaldehyde. Results: Our research showed that the main components of cinnamon, including cinnamaldehyde, can play a role in the treatment of breast cancer through 59 possible important targets. Subsequently, enrichment analysis by GO and KEGG showed that 83 cell biological processes and 37 pathways were associated with breast cancer (p<0.05), including peroxisome proliferator-activated receptor and PI3K-Akt pathway, which are closely related to tumor cell apoptosis. In vitro cell verification experiments showed that cinnamaldehyde can significantly inhibit cell proliferation, change cell morphology, inhibit cell migration and invasion ability, and promote cell apoptosis. Conclusion: Our results showed that cinnamaldehyde is a potentially novel drug for the treatment and prevention of breast cancer.